Unpacking Civil-Military Relations Trajectory in the New Dispensation in Zimbabwe - Marawako, Jonah; Mupasu, Tatenda Yvonne (International Journal of Law and Public Policy (IJLAPP), 2022)
The removal of Mugabe by the civil-military alliance ushered a new hope for improved civil-military relations in Zimbabwe. Prior to the coup, civil-military relations were strained and the military was unleashed by the government on the civilians to undermine democracy. During the ouster of Mugabe the military used the civilians to demonstrate thereby legitimising their putsch. There was euphoria among the civilians that this was the beginning of democracy and the stabilisation of civil-military relations. However the exultation suffered from stillbirth as the military continued with its traditional practice of untethering violence and coercion on the civilian, in the post-Mugabe epoch militarisation reached its crescendo. This research analyses civil-military relations in the context of the role of the military in the 2018 elections, militarisation of artisanal small-scale mining in Zimbabwe and the collision of militarisation and state capture. This paper argues that the political vicissitude heralded the military-executive alliance that employs an orgy of violence on the civilians hence this exacerbates strained civil-military relations in Zimbabwe and cast a horrendous situation for democracy in the future. The Corona virus 2019 (COVID 19) lockdowns rules and regulations have aggravated the relations as the military used comprehensive surveillance against the civilians.